A systematic review on malaria and dengue vaccines for the effective management of these mosquito borne diseases: Improving public health - Hind M. Al-Osaimi; Mohammed Kanan; Lujain Marghlani; Badria Al-Rowaili; Reem Albalawi; Abrar Saad; Saba Alasmari; Khaled Althobaiti; Zainab Alhulaili; Abeer Alanzi; Rawan Alqarni; Razan Alsofiyani; et al. (Human Vaccines & Immunotherapeutics)
Insect vector-borne diseases (VBDs) pose significant global health challenges, particularly in tropical and subtropical regions. The WHO has launched the “Global Vector Control Response (GVCR) 2017–2030” to address these diseases, emphasizing a comprehensive approach to vector control. This systematic review investigates the potential of malaria and dengue vaccines in controlling mosquito-borne VBDs, aiming to alleviate disease burdens and enhance public health. Following PRISMA 2020 guidelines, the review incorporated 39 new studies out of 934 identified records. It encompasses various studies assessing malaria and dengue vaccines, emphasizing the significance of vaccination as a preventive measure. The findings indicate variations in vaccine efficacy, duration of protection, and safety considerations for each disease, influencing public health strategies. The review underscores the urgent need for vaccines to combat the increasing burden of VBDs like malaria and dengue, advocating for ongoing research and investment in vaccine development.